The preparation and utilization of langka powder - Elefano, Rosario Principe 1941-; Guzman, Matilde P. ([Queon City], 1961)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Literature cited: l. 30-32.
Thesis (B.S. Food Tech.)--University of the Philippines.
Keywords: Jackfruit, Dried